The return of religion - Griffioen, S. (Koers, 2011)
Religion is back in Philosophy as a respectable subject. Part 1 first charts what MacIntyre, Taylor and Derrida have meant in this regard. Subsequently, it turns to the Enlightenment to determine what constituted the breakthrough. It is found that even where the Enlightenment gave maximum room to religion i.e. as a civic religion and as “religion of the heart”) it still excluded a constitutive relation to a transcendent revelation. Part 2 centres on the religion-faith distinction in reformational philosophy. Similar to the Enlightenment, religion is understood as part of human nature. However, human nature itself is conceived as intrinsically religious and depending for its light on revelation. Secondly, “religion” in this context also encompasses idols and religious substitutes. Thus, it directs attention to shopping malls, football stadiums, health policy, et cetera, as possible contexts of a return of religion. Examples show that this has become a popular approach. However, most of the publications surveyed fail to distinguish between an “analogical” and a “pistically qualified” use of religion, and are open to exaggerations (the shopping mall and football stadiums as temples, etc.). At this junction, the relevance is shown of the religion-faith distinction as well as of Elaine Botha’s theory of metaphors. The epilogue offers an integration of parts one and two.